Effect of nano- and micro-sized Si3N4 powder on phase formation, microstructure and properties of β′-SiAlON prepared by spark plasma sintering. Issue 2 (15th January 2022) - Bake, Abdulhakim; Hakeem, Abbas Saeed; Ahmed, Bilal Anjum; Ul-Hamid, Anwar; Alhems, Luai M.; Ehsan, Muhammad Ali; Hashem, Mjed; Tanvir, M.T.; Hampshire, Stuart
Abstract: The phase formation behavior of β′-SiAlON with the general formula Si6-z Alz Oz N8-z was studied comprehensively for z values from 1 to 3 using spark plasma sintering (SPS) as the consolidation technique at synthesis temperatures from 1400 to 1700 °C. The samples were prepared close to the β′-SiAlON composition line: Si3 N4 − 4/3(AlN·Al2 O3 ) in the phase diagram using (A) nano-sized amorphous Si3 N4 and (B) micro-sized β-Si3 N4 precursors. Field-emission scanning electron microscopy (FESEM) was used for microstructural analysis. Most compositions reached almost full density at all SPS temperatures. Compared with the micro-sized β-Si3 N4 precursor, the nano-sized amorphous Si3 N4 precursor accelerated the reaction kinetics, promoting the formation of dense β′-SiAlON + O′-SiAlON composites after SPS at synthesis temperatures of 1400–1500 °C. This resulted in very high values of Vickers hardness (Hv10 ) = 18.2–19.2 GPa for the z = 1 composition related to the hardness of the O′-SiAlON component phase. In general, for samples synthesized from nano-sized amorphous Si3 N4, which were almost fully dense, containing >95% β′-SiAlON, the hardness values were 13.4–13.8 GPa with a fracture toughness of 3.5–4.6 MPa m 1/2 . For equivalent samples synthesized from micro-sized β-Si3 N4, hardness was in the range 13.9–14.4 GPa with a fracture toughness of 4.3–4.5 MPa.m 1/2 . These values are comparable with fully dense β′-SiAlONs, usually containing intergranular glass phase which has been sintered by HIP and other processes at much higher temperatures for longer times. Highlights: β′-SiAlONs with different z values were prepared via SPS technique using nano-sized amorphous Si3 N4 and micro-sized β-Si3 N4 . The starting powder size governed the synthesis reaction rate and mechanical behavior. Rapid densification occurred at all temperatures for all z values for both types of silicon nitride precursors. Amorphous Si3 N4 facilitated rapid reaction to form β′-SiAlON and O′-SiAlON, resulting in improved mechanical properties. In the current study, β′-SiAlONs are processed at much lower temperatures and shorter time to achieved comparable properties.